Burn-in : a novel of the real robotic revolution - Singer, P. W. (Peter Warren); Cole, August (Boston; New York : Houghton Mifflin Harcourt, 2020)
"An FBI agent teams up with the first police robot to hunt a shadowy terrorist in this gripping technothriller-and fact-based tour of tomorrow-from the authors of Ghost Fleet"--
Keywords: Mystery fiction; Science fiction